Comparison of clinical results after augmented versus direct surgical repair of acute Achilles tendon rupture - Leigheb, Massimiliano; Guzzardi, Giuseppe; Pogliacomi, Francesco; Sempio, Luca; Grassi, Federico A. (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Achilles tendon rupture is frequent and can result in a disabling condition. The ideal method of management remains a matter of debate. We aimed to compare the clinical outcome of patients who underwent surgical repair of Achilles tendon rupture with Silfverskiöld augmentation technique with gastrocnemius fascia flap versus Krackow end-to-end stitching technique. Methods: We retrospectively studied all patients that were surgically treated for Achilles tendon rupture at our institution, between January 2000 and December 2015, using either Silfverskiöld or Krackow technique. We excluded all patients deceased or untreaceble, and those refusing the follow up interview. Disability, Quality-of-Life and functional restriction were evaluated using the Achilles-Tendon-total-Rupture-Score (ATRS) and Foot-and-Ankle-Disability-Index (FADI); means were compared by the Mann-Whitney test and correlations by the Spearman coefficient. Results: A total of 90 patients were included, with a mean age of 45.3±12.6 years. The augmented repair group-A included 33 patients and the simple repair group-B 57 patients. Follow-up averaged 8 years (1 to 16). FADI was 103.7±1.6 for group-A versus 100.3±15.6 for group-B. ATRS was 2.0±7.1 and 5.7±18.8, respecitvely. Differences were not significant. Age showed a low linear correlation with ATRS (R=0.41) and FADI (R=-0.40), indicating that clinical outcomes minimally tend to worsen in older patients. Conclusions: We didn’t find significative differences in the clinical outcomes between the two groups of patients. Acute uncomplicated Achilles tendon ruptures can be successfully treated with a direct suture technique. Augmentation with a fascial flap should be reserved to chronic or neglected cases with severe tendinosis or tissue defect.